Inhibitors of 20-hydroxyeicosatetraenoic acid (20-HETE) formation attenuate the natriuretic effect of dopamine - Federik Fernandez, Maria M. (2012)
Endogenous renal dopamine is a major physiological regulator of renal ion transport; however its intracellular signaling pathways are not thoroughly understood. The present study examined the role of 20-hydroxyeicosatetraenoic acid (20-HETE), the major cytochrome P450 (CYP4A) metabolite of arachidonic acid formed in the renal cortex, on the natriuretic response to dopamine in Sprague Dawley rats. Infusion of dopamine (1.5 μg/kg/min, i.v.) increased urine flow (1.9 fold over basal), sodium excretion (UNaV, 2.7 fold), fractional sodium excretion (FENa, 3.3 fold) and proximal and distal delivery of sodium by 1.5- and 2-fold respectively. Administration of two inhibitors of the synthesis of 20-HETE, 1-aminobenzotriazole (ABT) and N-hydroxy-N′-(-4-butyl-2- methylphenyl)formamidine (HET0016) reduced the response to dopamine by 65%. Induction of the renal expression of CYP4A enzymes with clofibrate did not alter the response to dopamine. The natriuretic response to dopamine was lower in Dahl salt-sensitive rats in comparison to an SS.BN5 consomic strain in which transfer of chromosome 5 from Brown Norway to Dahl salt-sensitive rats upregulates the renal expression of CYP4A protein and the production of 20-HETE. Treatment with HET0016 blocked the renal effects of dopamine in SS.BN5 rats. We also examined the influence of 20-HETE in the natriuretic response to acute volume expansion that is in part mediated via the release of endogenous dopamine. The increase in urine flow, UNaV, FENa and distal FENa following volume expansion was markedly reduced in rats treated with ABT. These results suggest that 20-HETE plays at least a permissive role in the natriuretic response to dopamine.